Short Communication: Studying the Role of Smart Flare Gold Nano Particles in Studying Micro RNA and Oncogene Differential Expression in Prostate Cancer Cell Lines (Journal of Cancer Research Updates, 2017)
Nano technology is a cutting edge science which is now effectively used in the field of cancer biology. Smart Flare gold nanoparticles are now used often for differential gene expression analysis. In this manuscript we are reporting the use of micro RNA miR 146a and onco gene EZH2 Smart Flare probes to study their expression in different prostate cancer cell lines and the effect of novel Rhenium compounds on these genes using a flow cytometer and a Fluorescence microscope. Our results showed this novel nanotechnology can be effectively used in cancer biology to successfully detect the effect of novel drugs on oncogenes and could be a very useful tool for next generation of cancer researchers.